Differences in the game specific skills of elite and sub-elite youth football players: Implications for talent identification - Waldron, M.; Worsfold, P. (International Journal of Performance Analysis in Sport, 2010)
The concept of multidimensional talent modelling offers a recent attempt to objectively identify sporting talent in adolescents, of which game specific skill assessment has become a significant dimension. Previous studies have used closed skill testing to assess 'open' skills in youth football players, often finding such measures to discriminate between elite and sub-elite groups. The current study used an example performance analysis template to; 1) Identify differences in performance indicators between pre-determined groups of elite and sub-elite performers during an open match environment; 2) Identify differences in performance indicators between positional groups of elite and sub-elite performers at separate levels of competition; 3) Individually identify sub-elite players compared to a normative profile of elite positional counterparts. Results from Mann-Whitney U testing suggested that elite players are significantly higher (p<0.0028) performers within 9 of 18 performance indicators. Comparisons refined by position and round of competition found only one indicator to distinguish between elite and sub-elite players. The use of a normative profiling method demonstrated how sub-elite players may be analysed relative to elite counterparts. Results are discussed in relation to the advantages of performance analysis as a preferred measure of game specific skills in the talent identification process.